Effectiveness of Virtual Reality in the Rehabilitation of Motor Function of Patients With Subacute Stroke: A Meta-Analysis - Peng, Quan-cheng; Yin, Ling; Cao, Yi (Frontiers in Neurology, 2021)
Stroke is a major cause of death and disability in adults. Conventional therapy (CT) has limited effectiveness, and therefore, various virtual reality (VR) rehabilitation programs have been designed. However, their efficacy in regaining motor function in patients with subacute stroke is questionable. Therefore, we conducted this meta-analysis to determine the efficacy of VR, compared to CT, in restoring motor function in this patient population. Up to October 10, 2020, nine electronic databases were searched for relevant articles reporting the effectiveness of VR in regaining motor function in patients with subacute stroke. This search was updated on March 7, 2021, with no additional added articles. The control group included CT, physical therapy, occupational therapy, or a combination of them. Effectiveness is defined as the positive change from baseline values to the last follow-up point. The Cochrane's revised risk-of-bias tool was used to determine the quality of included trials. A metaregression analysis was conducted to determine the effect of “time since last stroke” on reported outcomes. Publication bias and sensitivity analyses were also carried out. A total of 19 studies (17 randomized controlled trials, 1 cohort study, and 1 crossover trial) were included in the qualitative analysis, whereas 16 trials were meta-analyzed. A great improvement in motor function was noted in the VR group, when compared to preintervention values [standardized mean difference (SMD) = 1.14; 95% confidence interval (CI) = 0.77–1.52; I2 = 82%; P < 0.001]. When compared to CT, VR resulted in mild improvement in motor function (SMD = 0.47; 95% CI = 0.22–0.72; I2 = 75%; P < 0.001). However, upon trim-and-fill adjustment, this finding was deemed insignificant (SMD = 0.08; 95% CI = −0.16 to 0.33; I2 = 82.6%; P < 0.001). Ten studies had low risk, five had some concerns, three had high risk, and one had a moderate risk of bias. VR programs can be used jointly with CT for the rehabilitation of the motor function of patients with subacute stroke. However, more studies are still warranted to determine the effectiveness of these interventions in retaining the cognitive function and physical performance of such patients.